Influence Mechanism of Land Use/Cover Change on Surface Urban Heat Islands and Urban Energy Consumption in Severely Cold Regions - Jinjian Jiang; Jie Zhang; Peng Cui; Xiaoxue Luo (Land)
Intensifying global warming has disrupted natural ecosystems and altered energy consumption patterns. Understanding the impact of land use and cover change on surface urban heat islands (SUHIs) and energy use is critical for sustainable development. In this study, normalized difference vegetation index (NDVI), modified normalized difference water index (MNDWI), normalized difference built-up index (NDBI), and SUHI data were derived using GIS and remote sensing (RS) technology, and quantitative analysis was performed in combination with energy consumption data. The results revealed the following key findings. In summer, the NDVI exhibited a significant negative correlation with total urban building energy consumption (r = −0.52), whereas the NDBI and SUHI showed significant positive correlations (r = 0.72 and r = 0.67, respectively). Moreover, the SUHI served as a mediating role between land use/cover change and electricity consumption, with the direct effect accounting for 36% and the indirect effect accounting for 64% of the total effect. In contrast, the NDBI was significantly positively correlated with energy consumption in winter (r = 0.53). Spline regression analysis further revealed that every one-unit increase in this index corresponded to an increase of approximately 22 million kWh in summer EC and an increase of approximately 1.16 billion kWh in winter EC.